High Temperature-Induced Expression of Rice α-Amylases in Developing Endosperm Produces Chalky Grains - Nakata, Masaru; Fukamatsu, Yosuke; Miyashita, Tomomi; Hakata, Makoto; Kimura, Rieko; Nakata, Yuriko; Kuroda, Masaharu; Yamaguchi, Takeshi; Yamakawa, Hiromoto (Frontiers in Plant Science, 2017)
Global warming impairs grain filling in rice and reduces starch accumulation in the endosperm, leading to chalky-appearing grains, which damages their market value. We found previously that high temperature-induced expression of starch-lytic α-amylases during ripening is crucial for grain chalkiness. Because the rice genome carries at least eight functional α-amylase genes, identification of the α-amylase(s) that contribute most strongly to the production of chalky grains could accelerate efficient breeding. To identify α-amylase genes responsible for the production of chalky grains, we characterized the histological expression pattern of eight α-amylase genes and the influences of their overexpression on grain appearance and carbohydrate components through a series of experiments with transgenic rice plants. The promoter activity of most α-amylase genes was elevated to various extents at high temperature. Among them, the expression of Amy1A and Amy3C was induced in the internal, especially basal to dorsal, region of developing endosperm, whereas that of Amy3D was confined near the ventral aleurone. These regions coincided with the site of occurrence of chalkiness, which was in clear contrast to conventionally known expression patterns of the enzyme in the scutellum and aleurone during seed germination. Furthermore, overexpression of α-amylase genes, except for Amy3E, in developing endosperm produced various degrees of chalky grains without heat exposure, whereas that of Amy3E yielded normal translucent grains, as was the case in the vector control, even though Amy3E-overexpressing grains contained enhanced α-amylase activities. The weight of the chalky grains was decreased due to reduced amounts of starch, and microscopic observation of the chalky part of these grains revealed that their endosperm consisted of loosely packed round starch granules that had numerous pits on their surface, confirming the hydrolysis of the starch reserve by α-amylases. Moreover, the chalky grains contained increased amounts of soluble sugars including maltooligosaccharides at the expense of starch. The integrated analyses proposed that expression of Amy1A, Amy3C, and Amy3D at the specific regions of the developing endosperm could generate the chalkiness. This finding provides the fundamental knowledge to narrow down the targets for the development of high temperature-tolerant premium rice.